PENGARUH MEKANISME CORPORATE GOVERNANCE DAN KOMPENSASI EKSEKUTIF TERHADAP FEE AUDIT - Yolanda Bella Agnesia; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2020)
This study aims to discuss the effect of corporate governance and executive compensation on audit fees in developing countries. The variables used in this study are the dependent variable (audit costs), the independent variable (executive compensation, board independence and board ownership), moderation variables (audit risk) and control variables.The population in this study is manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018. Sampling is done by purposive sampling. Based on the purposive sampling method, samples obtained were 45 companies for the three years obtained (2016-2018). The analytical method used in this study is multiple regression analysis. In addition, the statistical technique used to test the hypotheses proposed in this study is panel data.The results of this study indicate that executive compensation, board ownership have a positive and significant effect on audit fees, and audit risk strengthens the relationship between executive compensation and audit fees. While, board independence is not significantly influence the audit costs.